The first option could be produced with the points (-1, -2) and (4, -3)
Explanation:
Step 1:
Assume
and
. So
and
.
The point-slope form is
.
Step 2:
First, we need to determine the value of the slope, m to substitute in the equation.
The slope is given by
.
![m=(-3-(-2))/(4-(-1)) = (-3+2)/(4+1)= -(1)/(5).](https://img.qammunity.org/2021/formulas/mathematics/high-school/994stdijhr0vd1yfkh2ojuz4ykpwjgzvii.png)
Step 3:
Substituting m's value in the equation, we get
For
,
.
For
,
![\left(y-y_(1)\right)=m\left(x-x_(1)\right) = \left(y-(-3)}\right)=-(1)/(5) \left(x-4}\right)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ecih34xgxv1mih45rn7674854loc1b1tgx.png)
.
The first option matches the calculated value
.